Structure-Based Mutational Analysis of the Bovine Papillomavirus E1 Helicase Domain Identifies Residues Involved in the Nonspecific DNA Binding Activity Required for Double Trimer Formation - Liu, Xiaofei (American Society for Microbiology (ASM), 2010)
The papillomavirus E1 protein is a multifunctional initiator protein responsible for preparing the viral DNA template for initiation of DNA replication. The E1 protein encodes two DNA binding activities that are required for initiation of DNA replication. A well-characterized sequence-specific DNA binding activity resides in the E1 DBD and is used to tether E1 to the papillomavirus ori. A non-sequence-specific DNA binding activity is also required for formation of the E1 double trimer (DT) complex, which is responsible for the local template melting that precedes loading of the E1 helicase. This DNA binding activity is very poorly understood. We use a structure-based mutagenesis approach to identify residues in the E1 helicase domain that are required for the non-sequence-specific DNA binding and DT formation. We found that three groups of residues are involved in nonspecific DNA binding: the E1 β-hairpin structure containing R505, K506, and H507; a hydrophobic loop containing F464; and a charged loop containing K461 together generate the binding surface involved in nonspecific DNA binding. These residues are well conserved in the T antigens from the polyomaviruses, indicating that the polyomaviruses share this nonspecific DNA binding activity.